Preliminary environmental scanning and SWOT analysis for Bicol's regional technology development strategies - Banzuela, Robert Ryan B. (University of the Philippines Diliman, 2012)
Bicol Region is one of the most gifted regions in the Philippines in terms of natural resources. However in terms of economic status, it remains one of the highest rated in poverty index as well as unemployment rate in the country. This paper is about identifying and analyzing the best path towards technological and economical development of Bicol region. Bicol region's being technologically challenged is one of the main problems that are plaguing the region. The region wasn't able to fully capitalize on its advantages to help the development of the region. In this paper, the region's best hope on poverty alleviation is Technology Development. Using the industry clustering method the niche industry will be determined. By targeting the Bicol region's key industries (aquaculture, agriculture and tourism), the region's technology development is the solution to the problem that is badly needed. Through the use of technology development, the region will be able to increase the output of these industries in the region and help raise the GDP of its constituents. Using the inter-relationship of Academic industry government, the region will be able to identify their roles and impact towards the success of technology and economic sustainable development of the region.